2020
DOI: 10.3340/jkns.2019.0161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cumulative and Conditional Antibiotic Release from Vancomycin-Embedded Fibrin Sealant and Its Antibacterial Activity : An In Vitro Study

Abstract: Objective : Fibrin sealants have been used for hemostasis, sealant for cerebrospinal fluid leakage, and adhesive barrier in neurosurgery. Further, as its clinical use and role of an effective drug delivery vehicle have been proposed. This study was performed to measure antibacterial activity and continuous local antibiotic release from different concentrations of vancomycin-impregnated fibrin sealant in vitro. Methods : Antibacterial activity was investigated by disk diffusion test by measuring the diameter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…[ 34 ] To determine the bactericidal activity of polymer materials, the disk‐diffusion method was used. [ 35 ] The disk diffusion test was used for the determination of the bactericidal activity of the polymers. Clean cultures of staphylococci sensitive to gentamicin ( Staphylococcus epidermidis 4743) and vancomycin ( Staphylococcus aureus 4766, Staphylococcus aureus 172) were used.…”
Section: Methodsmentioning
confidence: 99%
“…[ 34 ] To determine the bactericidal activity of polymer materials, the disk‐diffusion method was used. [ 35 ] The disk diffusion test was used for the determination of the bactericidal activity of the polymers. Clean cultures of staphylococci sensitive to gentamicin ( Staphylococcus epidermidis 4743) and vancomycin ( Staphylococcus aureus 4766, Staphylococcus aureus 172) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Vancomycin impregnated fibrin sealant was developed to measure antibacterial activity and antibiotic release. This study uses fibrin sealant as a topical hemostat for post-operatory treatments in surgical fields [126]. AgNPs were studied in metal/fibrin nanocomposites, recognized as suitable materials for wound healing.…”
Section: Fibrin-based Compositesmentioning
confidence: 99%
“…The study also assessed sustained vancomycin release from fibrin and disc diffusion assays were performed to detect vancomycin-resistant Staphylococcus aureus MRSA. Vancomycin release from fibrin glue lasted 14 days and the antibacterial activity was strong throughout the period [24]. It must be noted however that antibiotics added to components of fibrin glue may alter the physical properties of fibrin, e.g.…”
Section: Fibrin Glue As Carrier Of Active Substancesmentioning
confidence: 99%
“…The study of Kram et al demonstrated that gentamicin and neomycin extend clotting time. In conclusion, the properties of the clot as well as time of clot formation should always be checked in laboratory setting before using fibrin glue as a drug delivery system [7,14,[23][24][25].…”
Section: Fibrin Glue As Carrier Of Active Substancesmentioning
confidence: 99%